Perilaku Organisasi dan Budaya Organisasi terhadap Kinerja Pegawai - Antaris Fahrisani; Mokhammad Zulkarnain; Nursyamsu Nursyamsu; Siwi Woro Herningsih (IPM2KPE, 2022)
The purpose of this study is to analyze organizational behavior on employee performance, organizational culture on employee performance, organizational behavior, and organizational culture on employee performance. This research method is descriptive quantitative. The population of this study were employees at the Shipping Science Training Center (BP2IP) Tangerang, amounting to 30 people. The sample size is 30 people using the whole population sampling technique or the census technique. The results showed that there was a significant influence of organizational behavior on employee performance of 0.602 or 60.2%. There is a significant influence of organizational culture on employee performance at the Shipping Science Training Center (BP2IP) Tangerang by 0.520 or 52%. There is a significant influence of organizational behavior and organizational culture together on employee performance at the Shipping Science Training Center (BP2IP) Tangerang by 0.677 or 67.7%. In conclusion, the three research variables influence each other. Keywords: Organizational Culture, Employee Performance, Organizational Behavior